Pelatihan Literasi Informasi Berbasis Web: Sarana Perpustakaan Perguruan Tinggi Menyebarluaskan Koleksi - Ana Pujiastuti (IJAL (Indonesian Journal of Academic Librarianship), 2017)
ABSTRACT Advances in information technology presents opportunities for libraries to flourish, including on the type of collection. The digital collection comes as an alignment from a pre-existing print collection. The abundance of digital resources in libraries, either from purchases, local content, or cooperation results can be maximally utilized if there is knowledge. The process of transferring that knowledge will impact on a skill in utilizing knowledge resources. Web-based literacy training is a real application in college. How to transfer knowledge to earth and leverage thousands of digital collections that have been collected into the library collection. This web-based information literacy training is relevant to the characteristics of today's digital users who fall into the native digital category. How to learn this generation accustomed to fast paced and practical. This generation is very familiar with the technological sophistication. The task of librarians in this training activity is to direct the user to become a smart academic community in choosing, sorting and utilizing the flood of information resources on the internet. The success of this activity is supported by several factors, including: policies from stakeholders, librarian readiness, IT support, promotion. Hope with this web-based literacy training it is easier for visitors to get information relevant. So they can access, retrieve, answer scientifically. Keywords: information literacy; web-based information literacy; college libraries